CD6 attenuates early and late signaling events, setting thresholds for T-cell activation. - Oliveira, M; Gonçalves, C; Pinto, M; Fabre, S; Santos, A; Lee, S; Castro, M; Nunes, R; Barbosa, R; Parnes, JR; Yu, C; Davis, S; et al. (2012)
The T lineage glycoprotein CD6 is generally considered to be a costimulator of T-cell activation. Here, we demonstrate that CD6 significantly reduces early and late T-cell responses upon superantigen stimulation or TCR triggering by Abs. Measuring calcium mobilization in single cells responding to superantigen, we found that human T cells expressing rat CD6 react significantly less well compared with T cells not expressing the exogenous receptor. When the cytoplasmic domain of rat CD6 was removed, calcium responses were recovered, indicating that the inhibitory properties of CD6 are attributable to its cytoplasmic domain. Calcium responses, and also late indicators of T-cell activation such as IL-2 release, were also diminished in TCR-activated Jurkat cells expressing human CD6, compared with CD6-deficient cells or cells expressing a cytoplasmic deletion mutant of human CD6. Similarly, calcium signals triggered by anti-CD3 were enhanced in human T lymphocytes following morpholino-mediated suppression of CD6 expression. Finally, the proliferation of T lymphocytes was increased when the CD6-CD166 interaction was blocked with anti-CD166 Abs, but inhibited when anti-CD6 Abs were used. Our data suggest that CD6 is a signaling attenuator whose expression alone, i.e. in the absence of ligand engagement, is sufficient to restrain signaling in T cells.